Incidental Discovery of a Testicular Plasmacytoma at Initial Presentation of Multiple Myeloma - Amanda R. Hathaway (Case Reports in Hematology)
Testicular plasmacytomas are a rare phenomenon reported in the literature and they can occur as a solitary plasmacytoma, as a recurrence of multiple myeloma, or concurrently in an active myeloma. We report the case of a 43-year-old man who presented with back pain and was diagnosed with multiple myeloma. A CT scan performed to determine the extent of disease revealed an incidental mass in the testicle. Immunohistochemical staining of the mass revealed monoclonal cytolpasmic IgA in the tumor cells and serum studies showed this same immunoglobulin. Following orchiectomy, radiotherapy to the vertebra, chemotherapy with bortezomib, dexamethasone, and doxorubicin, and an autologous bone marrow transplant, the patient is alive twelve months after diagnosis and is in complete remission.